Tourism management evaluation in Mubi town Adamawa state Nigeria - Abdullahi, Hashim; Asmawi, M. Zainora; Abdul Aziz, Abdul Razak (O.P., 2023)
The tourism industry has both positive and negative environmental consequences which are the product of the managerial attitude. The study aims at evaluating tourism management in Mubi town Adamawa state Nigeria to make recommendations. Spatial and quantitative data are employed in the study. Geographical information systems (GIS) and remote sensing were utilized for the locational map generation with the aid of Arc. GIS.10.3. One hundred structured questionnaires were administered to the sample populations for the quantitative data generation using systematic random sampling techniques. Observations and photography were conducted as part of the data collection. A correlation descriptive statistical tool was used for correlating Environmental Tourism Potential (ETP) and Physical Tourism Potential (PTP). Statistical ranking techniques were utilized for the respondents’ perceptions results. The results of the descriptive statistics correlation between the tourism industry management (TIM) and physical tourism potentials (TPT) showed a very significant and perfectly positive correlation at (0.01 level, 2 –tailed). This indicated the correlation at positive at 0.01 and 2 Tailed. This uncovered a very strong connection between tourism industry management (TIM) and physical tourism potentials (TPT) in Mubi town. Additionally, the respondents quantitative ranking revealed that the tourism industry could create global interaction in Mubi town had the highest agreed responses. Tourism industry development could provide infrastructural facilities, employment opportunities, and revenue to the government in Mubi town followed as the second in the ranking. The third in the ranking is in Mubi town is yet to establish tourists’ information. Recommendations for infrastructural provision, staff employment, and development together with marketing are made.